2017
DOI: 10.1080/14786419.2017.1378202
|View full text |Cite
|
Sign up to set email alerts
|

Chemodiversity of Nepeta menthoides Boiss. & Bohse. essential oil from Iran and antimicrobial, acetylcholinesterase inhibitory and cytotoxic properties of 1,8-cineole chemotype

Abstract: The essential oil of Nepeta menthoides Boiss. & Bohse., from Iran, was analysed by GC/MS. Two types of multivariate analyses were done based on the chemical composition of the investigated sample in this study and 12 other samples reported in the literature to show the chemodiversity in essential oil composition. Antimicrobial, acetylcholinesterase inhibitory and cytotoxic activities of the essential oil and its major component were assessed. Twenty-one compounds were identified, representing 96.81% of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The major chemical compounds of AGO were 1,8-cineole (37.43%), 4-allylphenyl acetate (25.97%), and methyl eugenol (5.07%). AGO, 1,8-cineole, and methyl eugenol have been reported to have strong antibacterial and antifungal activities [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The major chemical compounds of AGO were 1,8-cineole (37.43%), 4-allylphenyl acetate (25.97%), and methyl eugenol (5.07%). AGO, 1,8-cineole, and methyl eugenol have been reported to have strong antibacterial and antifungal activities [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies showed the significant inhibition of AchE activity by essential oil and 1,8-cineole from N. menthoides. 1,8-Cineole exhibited higher inhibitory than the essential oil and both of them were more potent than rivastigmine (33). Taken together, these findings implicate that N. menthoides would be excellent candidate for future Alzheimer's disease therapy.…”
Section: Effect On Cognition and Memorymentioning
confidence: 71%
“…In 2018, Kahkeshani et al studied the inhibitory effects of the essential oil and 1,8-cineole isolated from N. menthoides against three breast cancer cell lines (MCF-7, T47D and MDA-MB-231). Both compounds displayed inhibitory activity, but the essential oil was more cytotoxic than 1,8-cineole to breast cancer cell lines (33).…”
Section: Cytotoxic Activitymentioning
confidence: 97%
“…The differences among the antimicrobial activities observed in the phenological stages, can be caused by the synthesis of volatile oil components with different rates. Important compounds such as borneol, camphor, menthone, menthol, and 1,8‐cineole have been reported to have antimicrobial activity. When all the basic compounds are evaluated, it can be said that these compounds are proportionally most synthesized at full flowering and post flowering stages.…”
Section: Resultsmentioning
confidence: 99%
“…Differently, it was reported that terpinene decreased to 32.41 % at post flowering stage in A. biebersteinii . In previous studies, it was found that the volatile oil had components with antimicrobial effect such as borneol, camphor, menthone, menthol, terpenen‐4‐ol, and 1,8‐cineole …”
Section: Introductionmentioning
confidence: 88%